Mathematics : a discrete introduction - Scheinerman, Edward R. ([S.l.] : Brooks Cole, 2000)
This book is an introduction to mathematics--in particular, it is an introduction to discrete mathematics. There are two primary goals for this book: students will learn to reading and writing proofs, and students will learn the fundamental concepts of discrete mathematics.